2022
DOI: 10.1007/s00404-022-06652-8
|View full text |Cite
|
Sign up to set email alerts
|

Offering women a choice in induction of labour: a prospective cohort study

Abstract: To evaluate women's choice in the method of labour induction between oral misoprostol, PGE2 pessary and the Foley catheter. To compare women's satisfaction according to their choice and to identify factors associated with patient satisfaction. MethodsWe conducted a comparative, prospective cohort study of 520 women who chose their preferred method for labour induction, in a French tertiary hospital, from July 2019 to October 2020. Before and after the delivery, they were asked to argument their choice and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Consistent with our findings, previously published studies have found a high degree of patient satisfaction regardless of cervical ripening setting. 19,[21][22][23][24] One study noted that although satisfaction was less for outpatients, patients in that group would opt for the same method and setting in subsequent pregnancies. 25 This discrepancy may relate to the finding that cervical ripening has been associated with a less positive experience of childbirth, regardless of method or setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, previously published studies have found a high degree of patient satisfaction regardless of cervical ripening setting. 19,[21][22][23][24] One study noted that although satisfaction was less for outpatients, patients in that group would opt for the same method and setting in subsequent pregnancies. 25 This discrepancy may relate to the finding that cervical ripening has been associated with a less positive experience of childbirth, regardless of method or setting.…”
Section: Resultsmentioning
confidence: 99%
“…25 This discrepancy may relate to the finding that cervical ripening has been associated with a less positive experience of childbirth, regardless of method or setting. 18,19,23,26 Qualitative feedback from participants provides a richer understanding of patients' behaviors during cervical ripening. Similar to the themes highlighted by our outpatients, Coates et al reported key themes of "ownership of induction of labor" and "importance of place" in patients undergoing outpatient cervical ripening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 80% of patients were satisfied with oral inductions, and 64% of patients stated that they would prefer to have the inducing agent given orally if they were to have another induction [ 10 ]. A French prospective cohort study of 520 women who chose their preferred method for labour induction showed that 67.5% of women chose oral misoprostol compared to 21% who chose a PGE2 pessary and 11.5% who chose a Foley catheter [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, data in the literature on women t satisfaction during induction of labor are scanty [13] , [14] , [15] . Few of them compare different methods of cervical ripening, with satisfaction as secondary outcome [16] , or by evaluating not only the induction but the whole childbirth [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%